การวิเคราะห์การไหลความเร็วสูงแบบอัดตัวได้ไร้ความหนืดโดยใช้เอลิเมนต์สี่เหลี่ยมและเทคนิคการปรับขนาดเอลิเมนต์ - วิทยา สดับสาร (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In this thesis, a finite element method for inviscid high-speed compressible flow using Taylor-Galerkin algorithm is presented. The algorithm has been developed using the four nodes quadrilateral element so that their closed-form finite element matrices can be derived. Such matrices with closed form expressions significantly reduce the analysis computational time as well as the required computer memory. The finite element equations corresponding to these flow problems were derived from the governing Navier-Stokes partial differential equations that consist of the conservation of mass, momentums, and energy. A corresponding of finite element computer program was developed and verified by solving problems that have exact solutions. To further improve the analysis solution accuracy, an adaptive meshing technique was also cooperated. A new mesh consists of small elements in the regions with large changes of the solution gradients and large elements in the other regions where the changes of solution gradients are small. Several problems were tested to demonstrate the capability of the Taylor-Galerkin finite element algorithm with adaptive meshing technique that can predict detailed high-speed flow behaviors past complex geometries.